Internal and socio-political factors on profitability of Islamic banks in Indonesia - Pratama, Mohammad Aditya; Oktaviana, Ulfi Kartika (LPPM ISNJ Bengkalis, 2025)
Purpose – The purpose of this study is to analyze the effect of third-party funds (TPF), operating costs, operating income (OCOI), capital adequacy ratio (CAR), non-performing financing (NPF), gender and political connections on the profitability of Islamic banks. Method – This study is quantitative. The population of this study was 14 Islamic banks in Indonesia. The sampling technique used was purposive sampling, which was used to sample seven Islamic banks. The data source used was secondary data in the form of annual financial reports of Islamic banks from 2014 to 2023. The data analysis technique used panel data regression analysis with the Eviews-12 analysis tool. Findings – The results of this study indicate that partially TPF, CAR, NPF, gender and political connections do not affect the profitability of Islamic banks. However, only OCOI has a negative effect on the profitability of Islamic banks. Simultaneously, TPF, OCOI, CAR, NPF, gender and political connections affect the profitability of Islamic banks. Implications – This study can provide insight and complement existing theories on factors that influence profitability. This study can be a reference for banks to maintain their profitability ratio.